2019
DOI: 10.1002/acm2.12573
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and validation of an intra‐fraction motion management system for masked‐based radiosurgery

Abstract: Purpose Characterize the intra‐fraction motion management (IFMM) system found on the Gamma Knife Icon (GKI), including spatial accuracy, latency, temporal performance, and overall effect on delivered dose. Methods A phantom was constructed, consisting of a three‐axis translation mount, a remote motorized flipper, and a thermoplastic sphere surrounding a radiation detector. An infrared marker was placed on the translation mount secured to the flipper. The spatial accuracy of the IFMM was measured via the transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The GK Icon™ (Elekta, Stockholm, Sweden) is the sixth-generation and most recent commercial model. This latest upgrade includes a cone-beam computed tomography (CBCT) module, permitting non-invasive immobilization utilizing frameless treatments without compromising sub-millimeter accuracy [ 2 , 3 ]. Frameless stereotactic radiotherapy (SRT) allows for custom-tailored utilization and opens many new indications for treatment on the GK system.…”
Section: Introductionmentioning
confidence: 99%
“…The GK Icon™ (Elekta, Stockholm, Sweden) is the sixth-generation and most recent commercial model. This latest upgrade includes a cone-beam computed tomography (CBCT) module, permitting non-invasive immobilization utilizing frameless treatments without compromising sub-millimeter accuracy [ 2 , 3 ]. Frameless stereotactic radiotherapy (SRT) allows for custom-tailored utilization and opens many new indications for treatment on the GK system.…”
Section: Introductionmentioning
confidence: 99%
“…The Icon is unique in that it utilizes on‐board cone beam computed tomography (CBCT) imaging system to enable fractionated and frameless treatments . The specifics on commissioning and QA for the Icon system can be found in the literature . Dose is calculated for Icon patients using the TMR10 algorithm .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have presented quality assurance (QA) procedures of the LGK Icon™ 4–9 . Zeverino et al .…”
Section: Introductionmentioning
confidence: 99%
“…discussed commissioning procedures of the LGK Icon™ 5 . Knutson et al described QA techniques for the IFMM system of the LGK Icon™ 6 . AlDahlawi et al reported the QA procedure for the GK Icon™’s CBCT system 7,8 .…”
Section: Introductionmentioning
confidence: 99%